To Her Credit : Women, Finance, and the Law in Eighteenth-Century New England Cities - Damiano, Sara T., 1986- (Book collections on Project MUSE., 2021)
"This is a study in the history of capitalism in the context of colonial New England. The author argues that colonial women's skilled labor undergirded the workings of financial networks and was instrumental in shaping the development of economic and legal systems. The author shows that the economies of the colonial port cities of Boston and Newport could not have functioned without women's labor and credit relationships"--